Effect of a targeted pain management protocol for the treatment of dermatitis interdigitalis contagiosa in Merino meat sheep in a tilt squeeze chute - Rachidi, Fanny; Wagner, Romy; Fieseler, Helena; Kaiser, Matthias; Müller, Hendrik; Podpečan, Ožbalt; Mielenz, Norbert; Gottschalk, Jutta; Einspanier, Almuth; Möbius, Gerd; Baumgartner, Walter; Starke, Alexander (Frontiers in Animal Science, 2022)
The effect of a targeted pain management protocol consisting of sedation and local anesthesia on the stress response to treatment of dermatitis interdigitalis contagiosa (DINCO) was assessed in sheep placed in dorsal recumbency. Blood cortisol concentrations were measured once a day (Day 3 to 2) and additionally on day 0, six times during the claw treatment (stress model). Twelve healthy sheep (control group; HEALTHY) and 36 sheep with DINCO, randomly allocated to one of three treatment groups, underwent the stress model with or without pain control: the XYLA-IVRA sheep were sedated with 2% xylazine hydrochloride (XYLA) and received retrograde intravenous regional anesthesia (IVRA); the IVRA sheep underwent IVRA and received a placebo instead of sedation; the PLACEBO sheep received placebos for sedation and IVRA. The HEALTHY sheep underwent sham claw treatment and received placebos. The cortisol concentrations were higher in sheep restrained in dorsal recumbency compared with the cortisol concentrations measured four hours later in standing sheep (HEALTHY 37.2 ± 3.3 ng/ml vs. 18.5 ± 3.3 ng/ml; DISEASED 34.0 ± 1.9 ng/ml vs. 17.6 ± 1.9 ng/ml; p < 0.001). The stress response of XYLA-IVRA (area under the curve; AUC = 34.9 ± 2.6 ng/ml) was reduced compared with the stress response of PLACEBO (AUC = 48.0 ± 2.6 ng/ml, p < 0.01) and HEALTHY sheep (AUC = 46.6 ± 2.5 ng/ml; p = 0.01). While cortisol concentration of XYLA-IVRA and HEALTHY sheep did not increase one day after the stress model (Day 1) compared with the day of the stress model (Day 0), both PLACEBO (47.4 ± 3.3 vs. 35.6 ± 3.1 ng/ml, p = 0.02) and IVRA sheep (39.1 ± 2.8 vs. 28.6 ± 3.1 ng/ml, p = 0.01) had higher cortisol concentrations. The results confirm that fixation in dorsal recumbency in a tilt squeeze chute was a major stressor in sheep. The differences in the cortisol concentration of the PLACEBO sheep versus the XYLA-IVRA sheep during and after the stress model illustrate the effect and necessity of pain management protocols in practice.